COMPARATIVE EVALUATION OF HAEMATOLOGICAL ARAMETERS IN HEALTHY AND PYOMETRA AFFECTED BITCHES - DABHI, D M; DHAMI, A J; PARIKH, P V; PATIL, D B (The Indian Journal of Animal Reproduction, 2023)
Haematological parameters were evaluated in 14 pyometra and 10 healthy bitches before and after ovario-hysterectomy. The Hb and TEC values were significantly (P< 0.01) lower in pyometra bitches than in healthy bitches. The mean PCV value was significantly (P < 0.01) higher and that of ESR lower in healthy bitches as compared to pyometra ones. There was slight improvement in the Hb, TEC and ESR at 15 days post-operative period, but not in PCV, in pyometra bitches. The values of PCV were identical, but the ESR was apparently higher in closed than the open pyometra. The mean TLC recorded in pyometra bitches was significantly (P < 0.01) higher than that in the normal bitches. Moreover along with a marked leucocytosis, neutrophilia ranging from 60 to 86 per cent was also observed in pyometra bitches. The mean percentage of neutrophil count was significantly (P < 0.01) higher (7 4.30 ± 1. 75 vs 57.80 ± 0.76 %) and lymphocyte counts lower (22.07 ± 1.59 vs 37.70 ± 0.58 %) in pyometra bitche than the normal ones. These findings were of prognostic value in diagnosing canine pyometra.